Rasionalitas Muslim : Perilaku Konsumsi dalam Prespektif Ekonomi Islam - Dewi Maharani; Taufiq Hidayat (ITB AAS INDONESIA Surakarta, 2020)
In the pursuit of economic activity, Islam porbids any elements related to it. Behavior of consumption in Islam is taught to In order for humans to consume their revenues or possessions for balance between the world and the next, by using the treasures earned to do good to fellow humans or other creatures on earth. The islamic view of economics is based on a paradigm of how to align people's interests more than personal ones. To see how consumption behavior in the perspective Islamic economics, the author wants to analyze rationally. The method used is library research because studies are focused on the materials Literature by poring over and studying the accepted literature.